The mediating role of affective commitment on the relationship between job satisfaction and turnover intention using structural equation modeling: Empirical evidence from Higher Education Institutions in Addis Ababa, Ethiopia - Kassahun T. Gessesse; Peteti Premanandam (Cogent Social Sciences, 2023)
Employee-organizational relationships can be assessed to achieve the goal of the organization in general and create a good working environment, specifically. However, studies were inadequate in higher educational institutions in Ethiopia. Therefore, this study examined the mediating effect of affective commitment on the relationship between job satisfaction and turnover intention among academic employees in higher education institutions in Addis Ababa. Full-time academic employees in higher educational institutions were the study population. The study used a quantitative research approach with a correlational research design. 319 respondents were selected using a proportional stratified random sampling method. Data were collected through structured questionnaires that were self-administered and analysed using structural equation modeling (SEM). This study found that affective commitment fully mediated the relationship between job satisfaction and turnover intention, as the direct effect between job satisfaction and turnover intention became insignificant at p < 0.05. Thus, research support and training and development initiatives for academic employees are recommended.